ҚАРАҚАЛПАҚСТАН РЕСПУБЛИКАСЫНЫҢ ТӘБИЙИЙ ФЛОРАСЫНДА ҚУРАМАЛЫГҮЛЛИЛЕР -ASTERACEAE D U M O R T ТУҚЫМЛАСЫ ЎӘКИЛЛЕРИНИҢ ТАРҚАЛЫЎЫ - Темирбеков, О. (FAN va JAMIYAT, 2024)
The article discusses the composition of Asteraceae Dumort species in the natural flora of the Republic of Karakalpakstan and distribution of the family across botanical and geographical regions.